Strategies for the successful lean manufacturing implementation: a case study in a Malaysian automotive parts manufacturing - Roslin, Eida Nadirah; Ahmed, Shamsuddin; Md Dawal, Siti Zawiah; Tamri, Norjamalullail (ESRSA Publications, 2012)
In recent global business environment, many manufacturing companies are attempting to implement lean manufacturing system. Malaysian manufacturing companies are no exception, and they consider lean manufacturing as an effective manufacturing strategy to survive in a highly competitive market. Given the lack of clear guidelines or step-by-step procedure in effectively implementing of lean manufacturing system among Malaysian manufacturing companies, this paper aims to present a case study of a manufacturing company pertaining to the automotive parts manufacturing company in Malaysia which has achieved significant improvement in productivity as a result of successful lean manufacturing implementation. The finding suggests that factors such as continuous management commitment, teamwork, and organization-wide involvement are crucial to lean success. The case study is expected to contribute important implications strategies for lean manufacturing system implementation in Malaysian manufacturing organization.